Clinical Diagnosis and Management of a Congenital Bilateral Wattle Cyst in a Kid - K, Gayathri; S, Anoop; Venugopal, Syam; Martin, K.D John (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Wattle cysts or tassel cysts are superficial swellings in goats, which normally appear apparently harmless to the quality of life of the species. A case of congenital bilateral wattle cyst in a kid with its clinical differential diagnosis, therapeutic management and clinical significance has been put on record in this communication.